2011
DOI: 10.1016/j.neuroimage.2010.10.074
|View full text |Cite
|
Sign up to set email alerts
|

Changes in brain network activity during working memory tasks: A magnetoencephalography study

Abstract: In this study, we elucidate the changes in neural oscillatory processes that are induced by simple working memory tasks. A group of eight subjects took part in modified versions of the N-back and Sternberg working memory paradigms. Magnetoencephalography (MEG) data were recorded, and subsequently processed using beamformer based source imaging methodology. Our study shows statistically significant increases in θ oscillations during both N-back and Sternberg tasks. These oscillations were shown to originate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
135
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(162 citation statements)
references
References 64 publications
20
135
5
Order By: Relevance
“…Compared to previous noninvasive studies based on scalp electroencephalography or magnetoencephalography (MEG) (Laufs et al, 2003;Mantini et al, 2007;Scheeringa et al, 2008;de Pasquale et al 2010;Brookes et al, 2011), the direct intracranial recordings used here allow for a higher spatial resolution particularly for deeper structures, and for the detection of electrophysiological correlates of the DMN at higher frequencies (up to 200 Figure 3. Single electrode data show suppression of gamma-band activity varies with task difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to previous noninvasive studies based on scalp electroencephalography or magnetoencephalography (MEG) (Laufs et al, 2003;Mantini et al, 2007;Scheeringa et al, 2008;de Pasquale et al 2010;Brookes et al, 2011), the direct intracranial recordings used here allow for a higher spatial resolution particularly for deeper structures, and for the detection of electrophysiological correlates of the DMN at higher frequencies (up to 200 Figure 3. Single electrode data show suppression of gamma-band activity varies with task difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, frontal theta activity has been linked to working memory and visual attention processes [40][42]. In addition, several studies have shown that frontal theta increases are correlated with memory load, in that larger memory loads (e.g., 5 items compared 3 items) are associated with stronger frontal theta activity [40][41], [43][44]. There is also some evidence that frontal alpha activity increases with memory load [42], although these reports have been less frequent.…”
Section: Discussionmentioning
confidence: 99%
“…Local increases in (frontal) theta have been observed in various memory and attention tasks during encoding, retention, and retrieval of information (e.g., Brookes et al, 2011;Gevins et al, 1997;Klimesch, 1999;Klimesch et al, 1996;Michels et al, 2008;Raghavachari et al, 2001;Sauseng et al, 2007;Sederberg et al, 2003), pointing to the involvement of frontal control processes in these tasks. WM load has been found to modulate frontal theta activity (Brookes et al, 2011;Jensen and Tesche, 2002). Furthermore, theta activity plays a major role in the integration of distributed neural information, such that interregional theta synchronization co-activates different brain regions (Sauseng et al, 2010).…”
Section: Oscillatory Neural Mechanisms Of Information Processing Relamentioning
confidence: 99%